Implementation of secondary school mathematics curriculum by teachers in two Malaysian schools - Lessani, Abdolreza (2015)
The aim of this study was to investigate the implementation of the components of the mathematics curriculum of two secondary schools in Malaysia. The objectives of this study were to investigate: i) teachers’ perceptions of the National Philosophy of Education; ii) teaching and assessment practices in 8th grade (Form 2) mathematics classrooms; and iii) contents of mathematics textbook in 8th grade (Form 2) in Malaysia,and compare with the contents of 8th grade (Secondary 2) mathematics textbooks in Singapore. This research was a qualitative case study. Two public secondary schools located in Serdang and Putrajaya were selected in the states of Selangor and the Federal Territory, respectively. The participants of this study were seven teachers of mathematics with at least three years of teaching experiences in 8th grade (Form 2), who were selected using the snowball sampling method. Data was collected using qualitative methods of interview, observation and document analysis in order to triangulate the data and ensure its validity. The interviews were conducted using a set of structured interview questions supplemented by video tape recordings and field notes. To establish quality of research findings, measures of credibilityand trustworthiness were strictly observed by the researcher. The data from the interviews and observations were categorized, coded, and grouped into themes based on qualitative analysis methods. Document analysis was performed to investigate the contents of mathematics textbook and Ministry of Education documents in Malaysia and Singapore, which was chosen as a source of comparison due to Singapore’s high ranking in Trends in International Mathematics and Science Study (TIMSS) results. The findings of the study showed that the teachers had moderate knowledge and understanding of the Malaysian National Philosophy of Education (NPE) and the aims and objectives of mathematics education. The overall results of the interviews and observations showed that the teachers partially followed the approaches in teaching mathematics as suggested by the Ministry of Education in Malaysia. Regarding the development of lesson plans and teaching based on the plans, almost all of the teachers used and followed lesson plans for their classes. The content of the textbooks in Malaysia (Form 2) and Singapore (Secondary 2) were analyzed and compared. The mathematics books were compared based on the four content domains of TIMSS which are Numbers,Algebra, Geometry and Data and Chance, and three cognitive domains which are knowing, applying, and reasoning. Overall, the result of this study revealed that the participants emphasized the importance of morality and belief in God among their students. The study also explored on the philosophy of education in Malaysia that aims to prepare students as balanced and harmonious individuals with a strong belief in God. Meanwhile, the aim of Singapore education is preparing students with the talent for the future of the country. The analysis of mathematics teachers’ assessment practices in this study showed the necessity of providing the teachers with more professional development and in-service training by the Ministry of Education (MOE) to improve their knowledge and skills in effective teaching and assessment practices, as well as applying new teaching methods, to improve the students’ achievements and the teachers’ teaching practices.